The Battle of Midway. - Symonds, Craig L. (Pivotal moments in American history., 2011)
There are few moments in American history in which the course of events tipped so suddenly and so dramatically as at the Battle of Midway. At dawn of June 4, 1942, a rampaging Japanese navy ruled the Pacific. By sunset, their vaunted carrier force (the Kido Butai) had been sunk and their grip on the Pacific had been loosened forever. In this absolutely riveting account of a key moment in the history of World War II, one of America's leading naval historians, Craig L. Symonds paints an unforgettable portrait of ingenuity, courage, and sacrifice. Symonds begins with the arrival of Admiral Cheste.